Lesbian, gay, bisexual, transgender and queer experiences of homelessness and identity: insecurity and home(o)normativity. Issue 2 (3rd April 2019) - Matthews, Peter; Poyner, Christopher; Kjellgren, Richard
Abstract: Homelessness among the young lesbian, gay, bisexual and trans* (LGBT+) population is becoming an increasing societal concern, with alarmist reporting of high rates of homelessness compared to heterosexual people. This paper presents qualitative evidence from research with 20 LGBT + people who had experienced homelessness in Scotland. Significantly, it moves discussion of LGBT + homelessness out of a concern with public health and social work, to understand it in terms of homelessness research and housing theory. The analysis also brings in queer theory to our discussions of homelessness and housing. As a result, rather than understanding our participants as passive victims of a homophobic or transphobic society, we focus on their agency in developing a queer identity alongside their experiences of insecure accommodation. In their experiences of homelessness people were carrying out 'edgework' at the margins of heteronormative society. Routes out of homelessness were thus associated with people becoming more comfortable within their identities. We conclude by arguing that experiences of homelessness interacted in complex ways with sexual and gender identity, and that tailored mainstream housing provision is required for LGBT + homeless people.